Abhisamãcãra: Personality Development Process according to Buddhism - Buakaew, Phra Somchai; WongKaew, Phramaha Boonsri; Ploychum, Suchao (Arts of Management Journal, 2021)
The objectives of this article were (1) to study personality development according to Western concepts, (2) to study Abhisamācāra in Buddhism, (3) to integrate the personality development process with Abhisamācāra in Buddhism, and (4) to propose the body of knowledge on “A model of personality development process integrated with Abhisamācāra”. The data of this qualitative study were collected from documents, research works, and in-depth interviews with 7 experts in personality development and 7 experts in Abhisamācāra. The data were analyzed and then presented in a descriptive method. The results of the study were found as follows: 1) Personality development is the process in behavioral adjustment suitably expressing to role, duty, and situation. 2) Abhisamācāra is the process of physical, verbal, and mental development based on the discipline set down by the Lord Buddha as a guideline for virtue cultivation for monks, leading to confidence and faith in people. 3) Physical integration is bodily action development with the realization of rules, regulations and culture in the society. Verbal action management is to realize language and communication appropriateness, leading to public understanding, and public and righteous advantages. Emotional management is the control of pleasant object and unpleasant object affecting bodily and verbal expressions. Social component management is to understand the personality expressions suitable to the contexts of community, tradition and culture by having interaction with respect and suitability to one’s own status and other people in society. 4) The body of knowledge obtained from the study on “The personal development integrated with Abhisamācāra” can be concluded into “LOTUS MODEL”.